NEGARA VERSUS PASAR : STUDI KASUS PENYELEWENGAN PAJAK KEUNTUNGAN OLEH GOOGLE.INC TERHADAP BRITANIA RAYA TAHUN 2014-2015 - Abdul Rahman Hidayat (HI 16 UMY 163, 2016)
*163 The change which happens in world order as a whole both in economic/political or is referred as Globalization has led to various effect, such as progress in the economic field. This article attempts to explain that Google as a product of globalization plays an important role to support the economy of the UK. However, along the way, Google as a company that engaged in information services world has committed fraud in the earned income tax, arguing there is no international law regulating taxes yet. Therefore, the UK as host country of Google trying to arrange laws regarding the tax fraud (Diverted Profit Tax). This is one of the implications of applying the concept of globalization, which is Transformasionalist, at which a country will be able to maximize the benefits of globalization, in this case giving obligations / regulations and restrictions, which are regime that is based on efficiency and fairness.